The Effect of Probability and Good Corporate Governance (GCG) on Tax Avoidance in Listed Industrial Sector Companies in Indonesia Stock Exchange (BEI) - Hasbullah Hajar; Muhammad Iqbal; Muh Sajjaj Sudirman (IAIN Palopo, 2023)
The purpose of this research are to find empirical evidence of Good Corporate Responsibility (GCG) variabel, that consists of a board of commissioners and institutional ownership, also profitability variable can effect the tax evasion variable, which is the object of research are industrial corporate sector that listed on the Indonesia Stock Exchange (IDX). To determine the sample for this research, purposive sampling methode is used for. The kind of data from this study are secondary data which is collected from prospectuses, financial reports, and financial statement of companies. Furthermore, the research conducted shows that the elements of GCG, that is independent board of commissioners and institutional ownership have an effect on tax evasion. Meanwhile, the companies profitability has no effect on the tax avoidance variable.